Precedensowe fenomeny kultury w przestrzeni intertekstowej (na materiale publicystyki polskiej i rosyjskiej) - Szafernakier, Anna (Acta Polono-Ruthenica, 2006)
In the article is taken notice of precedential phenomenas of culture seen through intertextual process. The author thinks, that you can understand phenomena of culture similar to texts. On the basis of Russian and Polish contemporary publicistic texts, you can follow how phenomenas of culture chosen by the author function (Don Kichot, Calvary, Napoleon)